"Whose plan is it?" understanding how the goal pursuit of consumers and carers influence choices in the australian disability sector. (September 2021) - Souza, Flavio; Duff, Gordon; Swait, Joffre
Abstract: The National Disability Insurance Scheme (NDIS) is an ambitious Australian welfare program, with the goal of supporting 460, 000 people living with a disability. To promote individual choices, the NDIS allocates personalised budgets based on the goals of Participants (or their nominated Carers). This paper examines (a) the heterogeneity of personal preferences for support services in the disability sector, (b) whether the program is subject to dissonance in the evaluation of supports for allowing different decision makers as plan managers and (c) how the central role of personal goals impacts the choice outcomes of eligible NDIS Participants (and their nominated Carers). Our findings reveal the adoption of two distinct mindsets: (i) one that favours immediacy and disability-specific services and (ii) one that pursues higher-quality services and general life skills. Although being a Participant or Carer in itself did not influence the adoption of either mindset, the goals they pursued did. To ensure the NDIS delivers on its intended Participant-focused outcomes, our findings suggest the need to understand the goals pursued by NDIS decision makers. Our study contributes to the body of research that promotes customer-centric approaches in policymaking and develops a methodology that produces insights for policy makers, service providers, advocacy groups and other NDIS stakeholders.